Acoustic wave ducting along magnetic flux tubes in the sunspot regions - Singh R.N. (My University, 2025)
The acoustic waves generated in the solar atmosphere propagate globally as well as upwards. These waves interact with the solar magnetic field structures and are ducted upwards. The velocity of these modified acoustic waves is shown to vary in a modelled solar atmosphere. The solar plasma propagating upwards with these waves are likely to alter the observed features of spicules, granules, and supergranules during changing phases of sunspot regions. © 1992 Kluwer Academic Publishers.